2023
DOI: 10.1177/10738584231163460
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Glia and Brain Astroglia: Complex Communication in Health and Disease along the Gut-Brain Axis

Abstract: Several studies have provided interesting evidence about the role of the bidirectional communication between the gut and brain in the onset and development of several pathologic conditions, including inflammatory bowel diseases (IBDs), neurodegenerative diseases, and related comorbidities. Indeed, patients with IBD can experience neurologic disorders, including depression and cognitive impairment, besides typical intestinal symptoms. In parallel, patients with neurodegenerative disease, such as Parkinson disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Patients with neurodegenerative diseases often exhibit gastrointestinal disorders and those with inflammatory bowel diseases can experience neurological disorders. In these patients, for example, microglial cells appear to activate astrocytes (reactive astrocytes) that are implicated in perpetuating neuroinflammatory processes that contribute to apoptosis of oligodendrocytes and synaptic nerve degeneration ( 187 , 188 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Patients with neurodegenerative diseases often exhibit gastrointestinal disorders and those with inflammatory bowel diseases can experience neurological disorders. In these patients, for example, microglial cells appear to activate astrocytes (reactive astrocytes) that are implicated in perpetuating neuroinflammatory processes that contribute to apoptosis of oligodendrocytes and synaptic nerve degeneration ( 187 , 188 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This intricate network involves multiple nervous and immune systems and is influenced by the composition of the gut microbiota and its metabolites (Mayer et al 2022 ). Notably, the gut–brain axis contributes to regulating various physiological processes, including digestion, metabolism, the immune response, and mood (D’Antongiovanni et al 2023 ). Multiple communications of the gut–brain axis occur through several pathways, such as neural connections, hormonal signaling, immune interactions, and microbial metabolites (Ancona et al 2021 ).…”
Section: Nds and Their Pathogenesismentioning
confidence: 99%
“…Disturbances in the gut are correlated with metabolic disorders. Several studies have reported the correlation between IBD, neurodegenerative, and neuroinflammatory diseases [ 95 , 96 ]. Recent population-based studies suggest that patients with IBD are at a high risk of developing PD [ 97 ].…”
Section: Effects Of Baicalin Functions On the Gut–brain Axismentioning
confidence: 99%